Influence of Microwave and Electron Beam Irradiation on Composition of Aluminum Nanopowder - Mostovshchikov A. V. Andrey Vladimirovich; Korshunov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich; Kalinich I. Ivan; Chumerin P. Yu. Pavel Yurievich (2018, 2018)
Title screen